2011
DOI: 10.1186/1471-2202-12-55
|View full text |Cite
|
Sign up to set email alerts
|

Learning alters theta amplitude, theta-gamma coupling and neuronal synchronization in inferotemporal cortex

Abstract: BackgroundHow oscillatory brain rhythms alone, or in combination, influence cortical information processing to support learning has yet to be fully established. Local field potential and multi-unit neuronal activity recordings were made from 64-electrode arrays in the inferotemporal cortex of conscious sheep during and after visual discrimination learning of face or object pairs. A neural network model has been developed to simulate and aid functional interpretation of learning-evoked changes.ResultsFollowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 49 publications
2
40
0
1
Order By: Relevance
“…Thus, single neuron firing and gamma are largest and convey the most content-specific information at particular frequencies and phases, suggesting that assemblies are organized by the frequency and phase of low-frequency oscillations [47,51]. Given that single-unit phase-locking [33] and PAC [52-54] are strongly associated with learning, they may also serve to transform sensory representations into frequency and phase-coded engrams.…”
Section: Frequency and Phase Specific Assembly Coding For Percepts Anmentioning
confidence: 99%
“…Thus, single neuron firing and gamma are largest and convey the most content-specific information at particular frequencies and phases, suggesting that assemblies are organized by the frequency and phase of low-frequency oscillations [47,51]. Given that single-unit phase-locking [33] and PAC [52-54] are strongly associated with learning, they may also serve to transform sensory representations into frequency and phase-coded engrams.…”
Section: Frequency and Phase Specific Assembly Coding For Percepts Anmentioning
confidence: 99%
“…Recently, more and more evidence suggests that corresponding CFC between these frequency bands plays a crucial role in this and other processes, e.g., neuronal computation, communication, and learning (Schack et al, 2002; Schack and Weiss, 2005; Canolty et al, 2006; Jensen and Colgin, 2007; Cohen, 2008; Tort et al, 2008, 2009; Doesburg et al, 2009; Canolty and Knight, 2010; Kendrick et al, 2011). In the study of Schack et al (2002), increased power in the theta and the gamma frequency bands was accompanied by strong phase coupling by means of cross- BIC between theta frequency at Fz and gamma frequency at F3 and Fp1, respectively, for memorizing number words.…”
Section: Theta-gamma Oscillatory Couplingmentioning
confidence: 99%
“…Although theta waves have been associated with both inhibitory and excitatory connections (Kendrick et al 2011), our observed increased ratio of excitatory to inhibitory composition with chronic stimulation suggests that less inhibitory drive contributes to the increased theta power.…”
Section: Discussionmentioning
confidence: 67%